Percepción de informantes claves y calificados sobre el potencial de focos de Contaminación Visual de origen publicitario en Avenida San Martin, Asunción, Paraguay (Journal on studies and research of academic knowledge, 2019)
Visual pollution causes negative impacts on the environment and also affects people, it can be caused by various factors, including the inappropriate presence of advertising posters on a site. In Paraguay few is mentioned of this type of pollution, although it is one of the most common in cities, for this reason the need arose to analyze the possible presence of sources of visual pollution of advertising origin,  in a section of  Avenue San Martin in the city of Asunción. As a research method in the present study, interviews were conducted to find out the opinion of the key and qualified informants regarding the posters located in the study sites, to identify the perception of this group of people regarding whether or not they consider the posters of the site as potential visual contaminants, and why. Among the most outstanding results of this study, it can be indicated that more than half of the interviewees perceived that the studied site could be considered to have the potential presence of visual contamination of advertising origin, and also that it was due to the number of posters present that they considered which had a harmful influence and caused over-excitement. Based on the results obtained, it can be asserted that there are sufficient reasons to consider that there are potential sources of visual contamination in the study area, therefore measures and actions must be planned to protect the site, to avoid damage to the environment. and the quality of life of people.
Keywords: visual pollution; advertising posters; perception; environment; quality of life